Effects of Sling and Core Strengthening Exercises on Transversus Abdominis Thickness and Endurance - Lee, Muryeol; Kim, Yongyoun; Ahn, Ilhwan; Kim, Bokyung; Kim, Nyeonjun; Koo, Japung; Gim, Mina (Journal of International Academy of Physical Therapy Research, 2025)
Background: Research comparing the relative effects of sling exercises and core exercises on transversus abdominis thickness and muscular endurance in adult males and females is still limited. In particular, more studies are needed to clarify the differences in muscle responses according to sex and to establish concrete evidence on how changes in transversus abdominis thickness correlate with improvements in functional endurance. Objectives: To investigated the effects of sling exercises and mat-based core exercises on transversus abdominis thickness and muscular endurance in adult males and females, and to propose effective core exercise strategies. Design: A randomized controlled trial. Methods: A total of 46 adult males and females in their 20s participated in either mat exercises or combined mat and sling exercises, performed twice a week for 30 minutes over a period of four weeks. Transversus abdominis thickness was measured using ultrasound, and muscular endurance was assessed using the Bourban test before and after the intervention. Withingroup changes were analyzed using paired t-tests, and between-group differences were analyzed using independent t-tests. Results: Both groups showed significant improvements in transversus abdominis thickness and muscular endurance after the intervention (P<.05). Both groups showed significant within-group improvements in transversus abdominis thickness (P<.05). Although the mat with sling exercise group showed a numerically greater increase, the between-group difference in the amount of change was not statistically significant (P=.122). While muscular endurance improved significantly in both groups, no significant difference was found between the groups. Conclusion: Mat with sling exercise and mat exercise can both be effective alternatives for enhancing transversus abdominis activation and improving muscular endurance. KCI Citation Count: 0